2015
DOI: 10.1021/acschemneuro.5b00035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of M4 Muscarinic Receptor Positive Allosteric Modulators Derived from VU10004

Abstract: The M4 mAChR is implicated in several CNS disorders and possesses an allosteric binding site for which ligands modulating the affinity and/or efficacy of ACh may be exploited for selective receptor targeting. We report the synthesis of a focused library of putative M4 PAMs derived from VU10004. These compounds investigate the pharmacological effects of target thieno[2,3-b]pyridines assembled from primary cycloalkanamines and cyclic secondary amines providing useful estimates of affinity (KB), cooperativity (αβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Huynh et al reported useful information on parameters for the investigation of allosteric modulator activity. 64) These parameters are the affinity of the allosteric ligand for the free receptor (KB); the cooperativity factors that define the magnitude and direction of the allosteric ligand's effect on the orthosteric ligand's affinity (α) and/or downstream efficacy (β); and the intrinsic agonist efficacy of the allosteric ligand (τB). It is worth mentioning that all synthesized compounds that demonstrate PAM activity of the M 4 mAChR also exhibit intrinsic activation (τB) at the allosteric site in their own right.…”
Section: )mentioning
confidence: 99%
“…Huynh et al reported useful information on parameters for the investigation of allosteric modulator activity. 64) These parameters are the affinity of the allosteric ligand for the free receptor (KB); the cooperativity factors that define the magnitude and direction of the allosteric ligand's effect on the orthosteric ligand's affinity (α) and/or downstream efficacy (β); and the intrinsic agonist efficacy of the allosteric ligand (τB). It is worth mentioning that all synthesized compounds that demonstrate PAM activity of the M 4 mAChR also exhibit intrinsic activation (τB) at the allosteric site in their own right.…”
Section: )mentioning
confidence: 99%
“…Positive allosteric modulators (PAMs) of the muscarinic acetylcholine receptor subtype 4 (M 4 ) have garnered a great deal of attention and interest as next generation antipsychotics via a novel mechansim of action. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] From the first account of an M 4 PAM ligand, 1, the βamino carboxamide moiety (circled in red) was present, and this functionality was maintained through multiple iterations of advanced ligands 2-5 (either thieno [2,3-b]pyridine 2-carboxamides, e.g., 1 and 2, or thieno[2,3-c]pyridazines 6-carboxamides, e.g., 3-5) enroute to preclinical development candidates (Fig. 1).…”
mentioning
confidence: 99%
“…1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] While potent and highly selective M 4 PAMs resulted that provided critical in vivo target validation and enabled deep mechanistic studies, this chemotype engendered poor physiochemical properties and varible species-specific P-gp efflux liabilities. Only recently have alternative M 4 PAM chemotypes been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, the diversity and breadth of small molecule M 4 PAMs is quite limited, and challenged by many of the most concerning issues with allosteric modulators (non-obvious, subtle structural modifications that engender steep SAR, species differences in affinity/cooperativity and subtype selectivity, solubility, and/or P-gp-mediated efflux). 9–12 From the beginning, Lilly’s LY2033298 ( 1 ) demonstrated that major species’ disconnects in activity were possible with M 4 PAMs; 1,2 however, second generation M 4 PAMs, such as VU0152100 ( 2 , also know as ML108), 3,4 were similarly potent on human and rat M 4 , and displayed antipsychotic-like activity in rats by potentiation of receptor activation by endogenous acetylcholine (Fig. 1).…”
mentioning
confidence: 99%